2021
DOI: 10.1016/j.jaip.2020.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Increased Respiratory Viral Detection and Symptom Burden Among Patients with Primary Antibody Deficiency: Results from the BIPAD Study

Abstract: Background Patients with primary antibody deficiency (PAD) are at increased risk of respiratory tract infections but our understanding of their nature and consequences remains limited. Objective To define the symptomatic and microbial burden of upper airway infection in adults with PAD relative to age-matched controls. Methods Prospective 12-month observational study consisting of a daily upper and lower airway symptom score alongside fortnig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 38 publications
6
35
0
Order By: Relevance
“…Case control prospective studies performed in patients with primary antibody deficiencies have reported worsening of symptom scores from the participant’s baseline, with the impaired lung function associated with respiratory viral infections. Rhinovirus was the virus most frequently detected, as we have also observed [ 5 , 10 ]. These studies included a heterogeneity of diseases, such as combined immunodeficiency or immune dysregulation diseases, with immunological profiles similar to A-T [ 5 , 10 ].…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Case control prospective studies performed in patients with primary antibody deficiencies have reported worsening of symptom scores from the participant’s baseline, with the impaired lung function associated with respiratory viral infections. Rhinovirus was the virus most frequently detected, as we have also observed [ 5 , 10 ]. These studies included a heterogeneity of diseases, such as combined immunodeficiency or immune dysregulation diseases, with immunological profiles similar to A-T [ 5 , 10 ].…”
Section: Discussionsupporting
confidence: 62%
“…Rhinovirus was the virus most frequently detected, as we have also observed [ 5 , 10 ]. These studies included a heterogeneity of diseases, such as combined immunodeficiency or immune dysregulation diseases, with immunological profiles similar to A-T [ 5 , 10 ].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The most common respiratory virus isolated in this study was human rhinovirus (HRV), followed by adenovirus, respiratory syncytial virus, and seasonal coronavirus (non-pandemic). Using a multiplex PCR approach, this study also showed that HRV and H. influenzae might frequently co-occur in patients with PADs ( 40 ). Furthermore, prolonged shedding of HRV after an acute infection has been shown by another group in patients with CVID and XLA compared to healthy controls (40 days versus 10 days) ( 41 ).…”
Section: Introductionmentioning
confidence: 68%
“…Bacterial infections and bronchiectasis are more commonly seen in patients with low IgG levels ( 64 , 103 , 158 , 159 ). IgRT may not significantly reduce viral respiratory infections ( 40 ).…”
Section: Relationship Between Igg Levels and Infectionsmentioning
confidence: 99%